PENGARUH PENGGUNAAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR SISWA PADA MATERI ARITMATIKA SOSIAL DI KELAS VII SMP NEGERI 1 SIAU TIMUR SELATAN - Baule, Vani; Pesik, Anneke; Pitoy, Cori (SOSCIED, 2024)
This study aims to determine whether the average learning outcomes of students using the problem based learning model are higher than the average learning outcomes using the direct learning model on social arithmetic material. This study uses a quasi-experimental method, with a Post-test Only Control Group Design research design. The subjects of this study were students in class VII of SMP Negeri 1 Siau Timur Selatan, which consisted of two classes, namely class VIIA as an experimental class using the problem based learning model and class VIIB as a control class using the direct learning model. Data collection was obtained by giving a pest test to both classes after the treatment was carried out. Research statistics were analysed using the t-test, hear the tvalue = 3,349638 > ttable = 2,00665 means H0 is rejected. Thus it can be concluded that the average learning outcomes of students taught with the problem based learning model are higher than average learning outcomes of students taught with the direct learning model